2018
DOI: 10.1007/s00259-018-4058-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of 68Ga-PSMA PET/CT, 18F-sodium fluoride PET/CT and diffusion weighted-MRI at for the detection of bone metastases in biochemically recurrent prostate cancer

Abstract: Ga-PSMA PET/CT and F-NaF PET/CT showed comparable and high diagnostic accuracies for detecting bone metastases in PCa patients with BCR. Both methods performed significantly better than DW-MRI, which was inadequate for diagnosing bone metastases when conducted in accordance with European Society of Urogenital Radiology guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 39 publications
2
59
0
2
Order By: Relevance
“…In another study of 123 patients with relapsed PCa, PSMA-PET showed a higher detection rate than choline-PET/CT for bone lesions (98 vs. 64%), even though ultimately there were mismatches for both tracers (41). PSMA-PET/CT and 18FNa-PET/CT methods were comparable and performed significantly better than DW600-MRI, which was less adequate for diagnosing bone metastases when conducted in accordance with the European Society of Urogenital Radiology guidelines (48).…”
Section: Is There Bone Disease?mentioning
confidence: 98%
“…In another study of 123 patients with relapsed PCa, PSMA-PET showed a higher detection rate than choline-PET/CT for bone lesions (98 vs. 64%), even though ultimately there were mismatches for both tracers (41). PSMA-PET/CT and 18FNa-PET/CT methods were comparable and performed significantly better than DW600-MRI, which was less adequate for diagnosing bone metastases when conducted in accordance with the European Society of Urogenital Radiology guidelines (48).…”
Section: Is There Bone Disease?mentioning
confidence: 98%
“…The diagnostic performances of NaF, FCH and DW-MRI in this setting have already been published [7,9,30,31]. The accuracy of NaF in detecting bone metastases was found to be significantly better than that of DW-MRI in a recent prospective comparison of 68 PCa patients with BCR [7]. Langsteger et al observed a better lesion-based specificity of FCH compared to that of NaF (96% vs 91%, p = 0.033) for an equivalent sensitivity of 89% in the context of BCR [9].…”
Section: Imaging Performancesmentioning
confidence: 99%
“…18 F-sodium fluoride positron emission tomography/ computed tomography (PET/CT) (NaF), 18 F-fluorocholine PET/CT (FCH) and diffusion-weighted whole-body magnetic resonance imaging (DW-MRI) are three novel imaging techniques that are effective for the detection of PCa bone metastases and their results may impact the management of patients [6]. Their diagnostic performances in detecting bone metastases in PCa patients with first biochemical recurrence (BCR) have already been published [7][8][9]. However, to the best of our knowledge, their cost-effectiveness in this indication has never been compared.…”
Section: Introductionmentioning
confidence: 99%
“…This white paper comprises consensus recommendations on performance, quality standards, and reporting of WB MRI to accommodate the increased use of WB MRI. Of note, the current literature suggests that WB MRI may be less sensitive to current PET technologies for detection of PCa (8,9); however, more robust data are needed, particularly to evaluate a possible complementary role for MR and PET.…”
Section: Overview Of Available Imaging Modalities Mrimentioning
confidence: 99%